2007
DOI: 10.1007/s11705-007-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the rheological, phase morphologic, thermal and mechanical properties of poly(trimethylene terephthalate)/ethylene propylene diene monomer copolymer grafted with maleic anhydride/metallocene polyethylene blends

Abstract: AbstractsThe rheological, phase morphologic, thermal and mechanical properties of poly(trimethylene terephthalate)/ metallocene polyethylene (PTT/mPE) blends in the presence of ethylene propylene diene monomer copolymer grafted with maleic anhydride (EPDM-g-MAH) as compatibilizer are studied by means of a capillary rheometer, scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and thermogravimetric analyzer (TGA). Results suggest that the compatibility of PTT/mPE blends is improved grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Mingtao et al observed that the compatibility of poly (trimethylene terephthalate)/metallocene polyethylene (PTT/mPE) blends was improved with the addition of a compatibilizer ethylene propylene diene monomer copolymer grafted with maleic anhydride (EPDM‐ g ‐MAH). They explained this with the reduction in radius of the dispersed phase in the system when the compatibilizer (EPDM‐ g ‐MAH) is added into the blend . Similarly Khonadkar et al also reported that, as the organo clay constituents are added into the blend the dispersed phase domain size decreased due to the compatibilization action of clay .…”
Section: Introductionmentioning
confidence: 95%
“…Mingtao et al observed that the compatibility of poly (trimethylene terephthalate)/metallocene polyethylene (PTT/mPE) blends was improved with the addition of a compatibilizer ethylene propylene diene monomer copolymer grafted with maleic anhydride (EPDM‐ g ‐MAH). They explained this with the reduction in radius of the dispersed phase in the system when the compatibilizer (EPDM‐ g ‐MAH) is added into the blend . Similarly Khonadkar et al also reported that, as the organo clay constituents are added into the blend the dispersed phase domain size decreased due to the compatibilization action of clay .…”
Section: Introductionmentioning
confidence: 95%